Clinical Outcomes of Rose Bengal Mediated Photodynamic Antimicrobial Therapy on Fungal Keratitis with Their Microbiological and Pathological Correlation. (3rd July 2022) - Bagga, Bhupesh; Sharma, Savitri; Ahirwar, Lalit Kishore; Sheba, Esther; Vaddavalli, Pravin Krishna; Mishra, Dilip K
Abstract: Purpose: To report the clinical outcome of Photodynamic Antimicrobial Therapy (PDAT) with Rose Bengal (RB) used as an early adjuvant therapy in patients with fungal keratitis and their microbiological and pathological correlation. Methods: Patients with microbiologically confirmed fungal keratitis underwent PDAT-RB along with topical natamycin 5% drops hourly and oral ketoconazole 200 mg twice a day. This was performed by applying rose bengal (0.1%) to the de-epithelialized cornea for 30 minutes, followed by irradiation with a 6 mW/cm 2 custom-made green LED source for 15 minutes (5.4 J/cm 2 ). The corresponding fungal isolates were tested in vitro using PDAT-RB and corneal buttons were evaluated for correlation. Results: Following informed consent, seven patients (male-5, female-2, mean age 47.7 years) with fungal keratitis were recruited. There were 3 cases each of Fusarium and Aspergillus flavus and 1 case of Acremonium sp. The average vertical and horizontal diameters of the corneal infiltrate were 4.12 ± 0.55 and 3.99 ± 1.19 mm, respectively. The average depth of corneal involvement was 283 ± 75.27µ as measured by anterior segment OCT. The clinical resolution was achieved in the cases with Fusarium keratitis with an average time of 39 days. Three cases of A. flavus and a single patient with Acremonium keratitis worsened and needed therapeutic keratoplasty (TPK) for resolution. Post-TPK, the corneal tissues grew A. flavus in one out of three cases and Acremonium sp. in one case. In vitro PDAT-RB experiment was performed on the corresponding fungal isolates grown from the corneal scraping. PDAT-RB produced clear inhibition of Fusarium and Acremonium sp. with no effect on the growth of A. flavus. Histopathologically, 2 out of 4 (50%) corneal buttons showed fungal filaments. Conclusions: While the in vitro and in vivo results of PDAT-RB matched for Fusarium sp. and Aspergillus flavus keratitis being favourable in the former and non-favourable in the latter, these results were discrepant in Acremonium sp.